Metabolism of Natural Killer Cells and Other Innate Lymphoid Cells - Cong, Jingjing (Frontiers in Immunology, 2020)
Natural killer (NK) cells are the host’s first line of defense against tumors and viral infections without prior sensitization. It is increasingly accepted that NK cells belong to the innate lymphoid cell (ILC) family. Other ILCs, comprising ILC1s, ILC2s, ILC3s and lymphoid tissue inducer (LTi) cells, are largely non-cytotoxic, tissue-resident cells, which function to protect local microenvironments against tissue insults and maintain homeostasis. Recently, evidence has accumulated that metabolism supports many aspects of the biology of NK cells and other ILCs, and that metabolic reprogramming regulates their development and function. Here, we outline the current understanding of ILC metabolism, and describe how metabolic processes are affected, and how metabolic defects are coupled to dysfunction of ILCs, in disease settings. Furthermore, we summarize the current and potential directions for immunotherapy involving targeting of ILC metabolism. Finally, we discuss the open questions in the rapidly expanding field of ILC metabolism.